A study of superstrate amorphous silicon thin film solar cells and modules on flexible BZO glass. Issue 2 (2nd November 2016) - Duan, Juanmei; Fang, Xuyang; Wang, Weiyan; Wang, Minghua; Huang, Jinhua; Li, Hongjiang; Yang, Weiguang; Song, Weijie
Abstract : Flexible thin film silicon solar modules on heat‐resistant transparent flexible substrates are promising to achieve high efficiency by a combination of high‐quality silicon thin films and fully monolithic series integration. In this work, performance of superstrate hydrogenated amorphous silicon (a‐Si:H) thin film solar cells and modules on flexible glass using boron‐doped zinc oxide (BZO) front electrode have been investigated. Compared with conventional glass, BZO thin films on flexible glass exhibited mixed structure of large‐sized pyramid and small‐sized grain, preferential crystalline orientations of (100) and (110), relatively lower surface roughness and scattering ability. Accordingly, compared with conventional BZO glass, a‐Si:H thin film solar cells on flexible BZO glass exhibited a relative increase in open‐circuit voltage, fill factor, and efficiency of 2.0, 5.5, and 3.4%, respectively. Finally, ∼50 cm 2 flexible a‐Si:H thin film solar modules were prepared by fully monolithic series integration using laser scribing, and relatively higher efficiency was achieved by improving thin films uniformity.